Combinatorial application of cuminaldehyde and gentamicin shows enhanced antimicrobial and antibiofilm action on Pseudomonas aeruginosa - Chatterjee, Sudipta; Paul, Payel; Chakraborty, Poulomi; Das, Sharmistha; Das Gupta, Anirban; Roy, Ritwik; Malik, Moumita; Sarkar, Sarita; Sarker, Ranojit Kumar; Tribedi, Prosun (Folia microbiologica, 2024)
The emergence of biofilm-induced drug tolerance poses a critical challenge to public healthcare management. Pseudomonas aeruginosa, a gram-negative opportunistic bacterium, is involved in various biofilm-associated infections in human hosts. Towards this direction, in the present study, a combinatorial approach has been explored as it is a demonstrably effective strategy for managing microbial infections. Thus, P. aeruginosa has been treated with cuminaldehyde (a naturally occurring phytochemical) and gentamicin (an aminoglycoside antibiotic) in connection to the effective management of the biofilm challenges. It was also observed that the test molecules could show increased antimicrobial activity against P. aeruginosa. A fractional inhibitory concentration index (FICI) of 0.65 suggested an additive interaction between cuminaldehyde and gentamicin. Besides, a series of experiments such as crystal violet assay, estimation of extracellular polymeric substance (EPS), and microscopic images indicated that an enhanced antibiofilm activity was obtained when the selected compounds were applied together on P. aeruginosa. Furthermore, the combination of the selected compounds was found to reduce the secretion of virulence factors from P. aeruginosa. Taken together, this study suggested that the combinatorial application of cuminaldehyde and gentamicin could be considered an effective approach towards the control of biofilm-linked infections caused by P. aeruginosa.
Keywords: Microbial Sensitivity Tests; gentamiciny; cymeny; Humans; Drug Synergism; Benzaldehydes; mikrobiální testy citlivosti; lidé; antibakteriální látky; Gentamicins; Pseudomonas aeruginosa; faktory virulence; synergismus léků; Anti-Bacterial Agents; biofilmy; benzaldehydy; Cymenes; Virulence Factors; Biofilms